Facial Soft Tissue Profile Analysis in Mongolian Children - Purevjav, Erdenebulgan; Radnaadorj, Altanzul; Ganburged, Ganjargal; Mashbat, Badamtsetseg; Bazar, Amarsaikhan; Moriyama, Keiji; Gombojav, Bayasgalan (Central Asian Journal of Medical Sciences, 2020)
Objectives: The present study aimed to evaluate the specific variables of facial soft tissue changes in Mongolian children using angular and linear measurements. Methods: We studied the lateral cephalograms of 541 subjects (228 male and 313 females) having normal occlusion between the ages of 6 and 15 years. Two orthodontists read all radiographs to determine their cerebral vertebral maturation index (CVMI). The radiographs were digitized and cephalometric measurements were made. Results: The Gl'-Sn-Pg' angle for all participants was 170.2 ± 5.4°. The Nasofrontal Gl’-N’-Tn’ angle was 147.2 ± 7.6° for all participants. It decreased with CVMI stage for girls (p = 0.000). The Nasofacial angle Tn- N'- Pog' angle averaged 20.4 ± 7.7° for all participants. The Nasomental angle N'- Tn-Pog' angle on averaged 144.9 ± 4.3° for all participants. It decreased with the CVMI stage for girls (p = 0.000). The Mentocervical Tn-Pog Me-NTP angle was significantly larger in boys than girls (107.8 ± 8.6° vs. 105.3 ± 7.8°, p = 0.001). The Nasolabial angle Ls-Sn-Col angle averaged 100.8 ± 10.6° for all subjects. It decreased with the CVMI stage for both boys (p = 0.043) and girls (p = 0.021). The distance between the E line and TUL was significantly larger in boys than girls (1.7 ± 2.1 vs. 1.2 ± 2.0 mm, p = 0.004). It also significantly decreased with the CVMI stage for both boys (p = 0.033) and girls (p = 0.000). The space between the E line and TLL averaged 1.9 ± 2.0 mm for all subjects. It did not differ by gender. However, it decreased with the CVMI in both boys (p = 0.022) and girls (p = 0.006). Conclusions: We have provided important results for comparing cephalometric soft-tissue values in Mongolian children in this study. These results provide a valuable guide for orthodontic diagnosis and treatment in our country.